Identifikasi Risiko Kecelakaan Perlintasan Sebidang di Kota Madiun - Astuti, Septiana Widi; Dewi, Puspita; Nurhadi, Muhamad; Nopryanto, Windi; Cesarasyid, Muhammad Kesuma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Railroad level crossings are potential points that are prone to serious accident risks. As transportation infrastructure grows, the importance of safety at level crossings increases. The accident prediction equation developed by the United State Department of Transportation (U.S. DOT) is one of the most frequently used formulas due to its accuracy in predicting the number of accidents at level crossings. In this study, the calculation of hazard index and hazard index and probability of accidents for the next few years using the U.S. DOT formula approach at level crossings located in Madiun City, namely JPL 1, JPL 136 and JPL 138. Based on the results of the Hazard Index calculation, JPL 136 has the highest hazard index value of 194.859 followed by JPL 138 and JPL 1. The results of accident predictions for the next three years at both JPL 1, JPL 136 and JPL 138 are likely to occur 2 accidents at the crossing.